Ocimum sanctum as Inhibitor for Mild Steel Corrosion in Phosphoric Acid Medium - Muthukumar, M.; Chandrasekaran, V. (Asian Journal of Chemistry, 2010)
The inhibition effect of Ocimum sanctum on corrosion of mild steel in phosphoric acid solutions has been studied. The mass loss and polarization techniques were employed at 302-333 K. The inhibition efficiency increased with increase in concentration of inhibitors and decreased with rise in temperature from 302 to 333 K and in acid concentration from1 to 5 N. The adsorption of this compound on the mild steel surface from the acids has been found to obey Temkin's adsorption isotherm. The potentiostatic polarization results revealed that Ocimum sanctum is a mixed type inhibitor. The values of activation energy (Ea), free energy of adsorption (ΔGads), enthalpy of adsorption (ΔH) and entropy of adsorption (ΔS) were also calculated. The plots of Wf against time (d) at 302 K gives straight line, which suggested that it obeys first order kinetics and also calculate the rate constant (k) and half life period (t½).